The feasibility of degradable glass microspheres as transient embolic medical devices. (January 2021) - Doucet, Jensen; MacDonald, Kathleen; Lee, Changseok; Hana, Renato Abu; Soulez, Gilles; Boyd, Daniel
The deliberate occlusion of blood flow through transarterial embolization is currently being used to treat conditions ranging from hemorrhages to hypervascular tumors. Degradable, imageable high borate glass microspheres (BRS2) were developed and tested to improve lesion targeting and promote a temporary vascular occlusion which is sufficient for most embolization procedure. A 48 hour pilot study, in a swine renal model, was conducted to assess the embolization effectiveness and potential risks of this new embolic agent. Bilateral embolization of the caudal branch of the renal arteries using test and control particles were performed in 4 pigs. Embolization efficacy, recanalization and resulting ischemia were evaluated at different time frame (0, 24 and 48 hours). The primary outcomes for this study were the assessment of: (i) embolization effectiveness, and (ii) vessel recanalization. The test article was found to occlude vessels as effectively as the control microspheres, with the use of a smaller volume of microspheres. At the 24 hour time point, over 95% of the material was found to be completely degraded, although little to no recanalization was observed. This data suggests that BRS2 is an effective embolic agent, however further investigations into the method of delivery are required prior to clinical implementation.